Understanding the Impact of Air Quality on the Incidence of Polycyclic Aromatic Hydrocarbons (PAHs) - Chandrashekhar Ravishankar (Multidisciplinary Journal of Akseprin Indonesia, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are environmental contaminants predominantly linked to chronic respiratory diseases. Heightened epidemiological evidence demands a focused initiative to enhance knowledge about the impact of air quality on the incidence of certain PAHs in airborne particulates. Polycyclic aromatic hydrocarbons (PAHs) are linked to respiratory issues such as asthma, aggravation , chronic bronchitis, and emphysema. The study provides an overview of contemporary PAH exposure and its hazardous effects on the respiratory system. A literature search across four scientific databases identified 120 pertinent research publications that examine urine concentrations of diverse persistent PAHs and associated biomarkers. The study emphasized the hazards associated with PM2.5-PAH conjugates, which can induce mutagenesis, carcinogenesis, and teratogenesis; disrupt signaling pathways; and lead to oxidative stress, acute and/or chronic respiratory ailments, cognitive deficits, cardiovascular issues, and mortality. The research highlights the considerable toxicity of PAHs and their metabolites to the respiratory system, activating interrelated AhR/non-AhR signaling pathways that result in oxidative stress, immune system impairment, asthma/COPD, and cancer. The study mostly demonstrates favorable connections between PAHs and respiratory toxicity.